Commuting stress and role centrality : antecedents to work-school conflict - Chew, Ice Asher (2019)
As tuition fees and cost of living hike yearly, more college students work to support their education, living expenses and for some financial freedom (Beeson & Wessel, 2002). Employed undergraduates are presented with challenges in managing work and school demands, resulting in work-school conflict (Markel & Frone, 1998). The aim of the current research was to investigate two novel antecedents of work-school conflict: commute stress and role centrality. By investigating novel antecedents to work-school conflict, we may be able to suggest improvements to employed students’ well-being and performance in the two roles. We hypothesized that commuting stress and role centrality would positively predict work-school conflict. Additionally, we hypothesized an interactive effect such that the relationship between role centrality and work-school conflict becomes stronger for those who experience higher commuting stress. The study utilized several self-reported measures in a cross-sectional design. Multiple regression was used to analyze the proposed models while controlling for the chief predictor of role conflict, role demands. We found that commute stress predicts school-to-work conflict, but not work-to-school conflict. Also, the interaction between commute stress and work centrality predicted work-to-school conflict, but not school-to-work conflict. Overall, our findings suggested that the relationships between the antecedents (commute stress, role conflict) and work-school conflict differ across the two domains. The current study highlights the need for more studies on the antecedents to work-school conflict to better understand this unique but understudied population.